2022
DOI: 10.1007/s12016-021-08920-y
|View full text |Cite
|
Sign up to set email alerts
|

An Italian Multicenter Study on Anti-NXP2 Antibodies: Clinical and Serological Associations

Abstract: The identification of anti-NXP2 antibodies is considered a serological marker of dermatomyositis (DM), with calcinosis, severe myositis and, in some reports, with cancer. Historically, these associations with anti-NXP2 antibodies have been detected by immunoprecipitation (IP), but in the last few years commercial immunoblotting assays have been released. The aim of this collaborative project was to analyse the clinical features associated to anti-NXP2 antibodies, both with commercial line blot (LB) and IP. Myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In another study of anti-small ubiquitin-like modifier activating enzyme (SAE) in suspected inflammatory myositis [ 46 ], a higher cut-off on LIA >=36 units) yielded better agreement with IP. Similar limitations and approaches to LIA testing of anti-melanoma differentiation-associated protein (MDA5), anti-NXP2 (nuclear matrix protein) and anti-TIF1-γ (transcriptional intermediary factor) were reported by others [ 47 , 48 , 49 ▪ , 50 , 51 ]. A study of anti-HMGCR (3-hydroxy-3-methylglutaryl-coenzyme A reductase) antibodies showed that detection of anti-HMGCR autoantibodies using LIA had high estimated clinical sensitivity and good concordance with an in-house laboratory developed ELISA [ 52 ].…”
Section: Line Immunoassays and Enzyme Linked Immunosorbent Assaysmentioning
confidence: 59%
“…In another study of anti-small ubiquitin-like modifier activating enzyme (SAE) in suspected inflammatory myositis [ 46 ], a higher cut-off on LIA >=36 units) yielded better agreement with IP. Similar limitations and approaches to LIA testing of anti-melanoma differentiation-associated protein (MDA5), anti-NXP2 (nuclear matrix protein) and anti-TIF1-γ (transcriptional intermediary factor) were reported by others [ 47 , 48 , 49 ▪ , 50 , 51 ]. A study of anti-HMGCR (3-hydroxy-3-methylglutaryl-coenzyme A reductase) antibodies showed that detection of anti-HMGCR autoantibodies using LIA had high estimated clinical sensitivity and good concordance with an in-house laboratory developed ELISA [ 52 ].…”
Section: Line Immunoassays and Enzyme Linked Immunosorbent Assaysmentioning
confidence: 59%
“…However, in patients with CADM, we did not observe an increased prevalence of cancer, underscoring the notion that cancer screening should be conducted in all patients with DM, regardless of their clinical presentation or autoantibody profile. Finally, all patients with anti-NXP2 or -Mi-2 antibodies exhibited muscle involvement, which should always be investigated and treated in these subclasses of DM frequently characterised by severe muscle involvement (14,17,18).The primary factors affecting prognosis in DM patients, independently from other serological and clinical features, appear to be ILD and cancer, without differences among DM, HDM, and CADM. The latter finding was unexpected as CADM showed a higher prevalence of lung involvement and it might be due to unknown confounding factors or the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…It was found to be the only positive antibody in a patient with skin involvement. NXP2-positive cases have been reported to more frequently show typical manifestations of facial DM as a heliotrope rash ( p < 0.0001; OR 3.4, 95% CI 1.88–6.2) ( 49 ). Like many MSAs, its prevalence is highly variable, as is its association with the development of cancer ( 35 , 42 ).…”
Section: Discussionmentioning
confidence: 99%